Simple Market Equilibria with Rationally Inattentive Consumers - Matějka, Filip; McKay, Alisdair (American Economic Review, 2012)
We study a market with rationally inattentive consumers who are unsure of the terms of the offers made by firms, but can acquire information about the terms at a cost. In a symmetric equilibrium, the price set by firms is continuously increasing in the cost of information for consumers and decreasing in the number of firms operating. In addition, favorable a priori information about a firm leads it to set a higher price, and a new entrant can increase demand for incumbents. When consumers have heterogeneous costs of information, firms selling low-quality products may choose to set the highest prices.